PERBANDINGAN PERTUMBUHAN STREPTOCOCCUS MUTANS INA99 PADA BERBAGAI MEDIA PERBENIHAN PADAT - Yayuk Yuliarsi (Journal of Dentistry Indonesia, 2015)
Previous study shows that tryptone-yeast extract-cystine-sucrose is choice of the culture media for isolating and growing S. mutans serotype C, but the effectiveness in stepping up the recovery growth of the bacteria has never been compared with that of the blood agar added to yeast extract and sucrose. This study was come to find out the growth of S. mutans serotype-c with blood agar-yest extract-sucrose, S. mutans INA99 serotype-c is identified, sliced, and cultured into blood agar-yeast extract-sucrose, brucella agar blood-yeast extract sucrose, blood agar and tryptone-yeast extract-cystine-sucrose, each 4 slices. The average amount of blood agar colonies that grows after an incubation of 2x24 hours in an anaerob conditionof 37 C, diluted by 40 time is 4.890. In blood agar-yeast extract-sucrose, the average colony is 145.600, diluted 1.600 time. In brucella agar blood-yeast extract-sucrose, the average colony is 103.50, diluted 40 times. In tryptone-yeast extract-cystine-sucrose the average colony is 2.430, diluted 40 times. Statistical result shows that, there are significant difference (p=0.000) between the total colonies of S. mutans INA99 serotype c which grows on the different types of culture media. The largest amount of colony is present on blood agar-yeast extract-sucrose, the followed by brucella agar blood-yeast extract-sucrose, blood agar and tryptone-yeast extract-cystine-sucrose. Conclusion : blood agar which added yeast extract and sucrose is the best culture media for S. mutans INA99 serotype c growth.